Prospering the mosque with Jom Lepak@Masjid - Siti Sarah, Mohamad Rajimi (2018)
Pekan, 8 December – Islamic & Human Development Centre (PIMPIN) continue to expand its responsibility to communities the university with the organizing of Jom Lepak @ Masjid at Kg. Tanjung Agas Mosque in Pekan recently.